Anticoagulant drugs increase natural killer cell activity in lung cancer - Bobek, V; Boubelik, M; Fiserová, A; L'uptovcová, M; Vannucci, L; Kacprzak, G; Kolodzej, J; Majewski, A M; Hoffman, R M (Lung cancer (Amsterdam, Netherlands), 2005)
BACKGROUND: In preclinical studies in animal models and in initial clinical trials, anticoagulation drugs have been shown to be effective in the prevention and treatment of haematogenous metastasis, and in the prolongation of survival in animal models. However, only a few studies have been performed on the direct influence of anticoagulation drugs on the immune system. OBJECTIVE: The purpose of this study is to determine the effect of warfarin, unfractioned heparin, low molecular weight heparins (LMWHs), and acetylsalicylic acid anticoagulants on the functional activity of natural killer (NK) cells. PATIENTS AND METHOD: Cytotoxic activity in patients with early, operable stages of non-small-cell lung cancer was compared with healthy volunteers. Cytotoxic studies were also carried out in tumor-bearing animals. RESULTS: Lung-cancer patients were characterized by significantly lower NK cell cytotoxicity (7.07 +/- 3.15) than healthy donors (44.12 +/- 10.62, P < 0.001). NK cell activation was found in both in vitro experiments using peripheral blood mononuclear cells (PBMC) from healthy donors and ex vivo in lung carcinoma patients after treatment with unfractionated heparin and fraxiparine. Similarly, potentiation of NK cell activity in Lewis lung carcinoma-bearing mice was found after therapy with unfractionated heparin. NK cell activity is lower in lung cancer patients than in normal subjects. CONCLUSIONS: NK cell activation was increased by LMWHs. Other anticoagulants augment the effector function of NK cells in cancer patients and in an animal model of lung cancer. This is a novel effect of these compounds, which were thought previously to exert their effect only via their anticoagulant properties.
Keywords: nádory plic; nemalobuněčný karcinom plic; Lung Neoplasms; Humans; Case-Control Studies; Tumor Cells, Cultured; lidé středního věku; Carcinoma, Non-Small-Cell Lung; studie případů a kontrol; Female; Aged; senioři; lidé; zvířata; myši; Carcinoma, Lewis Lung; buňky NK; Mice; nádorové buňky kultivované; Killer Cells, Natural; ženské pohlaví; Male; Middle Aged; Animals; karcinom plic Lewisové; mužské pohlaví; antikoagulancia; Anticoagulants